The impacts of HF and VHF radiation towards preliminary breakdown events in lightning flashes - Ismail, Mohd Muzafar; Zakaria, Zahriladha; Abd Razak, Jeefferie; Junid, Ramli (Penerbit UTeM, 2019)
Even though the mechanisms pertinent to the generation of radiation in frequency range above 3 MHz (HF and VHF radiation) are not well understood, it is thought that this radiation is caused by the electrical breakdown of virgin air rather than by the high current pulses propagating in pre-existing channels. The data presented in this paper also show that more HF radiation (3 MHz) is generated during preliminary breakdown processes taking place inside clouds (probably associated with breakdown of virgin air) than during the subsequent return strokes that propagate along conducting channels. Moreover, we also observe that VHF radiation (30 MHz) only from Preliminary Breakdown (PB) events.